STUDI KONSEP SEDEKAH DAN INFAK DALAM DONASI PENGGEMAR KEPADA KONTEN KREATOR TIKTOK DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Husna, Raudatul; Apif, Muhammad (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2023)
This study discusses the concepts of sadaqah and infak in fan donations to TikTok content creators from the perspective of Islamic economic law. The purpose of this study is to determine the suitability of fan donations with the principles of sharia economic law, explain the concepts of alms and infak in Islam, and analyze the mechanism and method of fan donations in the TikTok monetization program. This research uses descriptive analysis method based on literature research. The results show that in TikTok's monetization program, there are mechanisms and ways of fan donation that allow content creators to receive financial support. The Live Gifting feature allows fans to give virtual gifts to creators during live broadcasts, while the Creator Fund program allows creators to make money through advertising and content views. Sponsored content is also a source of income for creators through partnerships with brands or companies. Fan donations to content creators in TikTok can be in accordance with the principles of Islamic economic law if they fulfill the following: sincere intentions, financial limits, and good purposes. The concepts of sadaqah and infak in Islam can be applied in the context of fan donations, by ensuring sincere intentions, giving to those in need, and maintaining social justice. This research provides a deeper understanding of fan donations in the context of TikTok from the perspective of religion and Islamic law. The results of this study can serve as a guideline for creators and fans in making donations that are in accordance with the principles of Islamic economic law. In addition, this research also provides insight into the mechanisms and ways of fan donations in the TikTok monetization program, which can help creators in optimizing their earning potential.